2014
DOI: 10.1073/pnas.1324240111
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin targets fundamental processes in a methane-producing archaeon, Methanocaldococcus jannaschii

Abstract: Thioredoxin (Trx), a small redox protein, controls multiple processes in eukaryotes and bacteria by changing the thiol redox status of selected proteins. The function of Trx in archaea is, however, unexplored. To help fill this gap, we have investigated this aspect in methanarchaea-strict anaerobes that produce methane, a fuel and greenhouse gas. Bioinformatic analyses suggested that Trx is nearly universal in methanogens. Ancient methanogens that produce methane almost exclusively from H 2 plus CO 2 carried a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Similarly, the properties and distribution of DFTR and the conditions prevailing in M. jannaschii's habitat lead to the proposal that this enzyme developed in the low redox environment of early Earth and gave rise to NTR. This implication fits the hypothesis that the Trx-based redox control developed on Earth long before oxygen appeared (20).…”
supporting
confidence: 88%
See 4 more Smart Citations
“…Similarly, the properties and distribution of DFTR and the conditions prevailing in M. jannaschii's habitat lead to the proposal that this enzyme developed in the low redox environment of early Earth and gave rise to NTR. This implication fits the hypothesis that the Trx-based redox control developed on Earth long before oxygen appeared (20).…”
supporting
confidence: 88%
“…Similarly, there have been several reports on the Trx and TrxRs of anaerobic archaea (9,15,(17)(18)(19)(20)(21)(22)(23), including the methanogenic archaea, which are strict anaerobes (9,17,18,(21)(22)(23). Recently, a proteomics study has shown that there is clear potential for a Trx-based global redox regulation of metabolism, including methanogenesis, in Methanocaldococcus jannaschii, a strictly anaerobic and deeply rooted hyperthermophilic methanogenic archaeon that lives in deep-sea hydrothermal vents (20). Two reports also describe the activation of deactivated methanogen proteins by thioredoxin (10,20).…”
mentioning
confidence: 90%
See 3 more Smart Citations